CLINICAL FEATURES OF ATYPICAL ANOREXIA NERVOSA IN ADOLESCENT GIRLS WITH OLIGO-AMENORRHEA - L. M. Lev; V. O. Andreeva; V. G. Zaika; A. S. Andreev; N. V. Tkachenko (Медицинский вестник Юга России, 2013)
Purpose: Based on the study of clinical features to identify diagnostic criteria for atypical anorexia nervosa (AN) for timely diagnosis and treatment in adolescent girls with oligo-amenorrhea.Materials and methods: I group - 18 patients with atypical AN, II group - 22 patients with a diagnosis of typical AN. The age of both groups 16 (18; 14) years. The body mass index I of group - 14,55 (17,34; 10,2), II - 15,6 (17,5; 11,6). Control group - 20 teenage girls.Conducted clinical-psychopathological, experimental psychological research, psychometric scaling. Results: differences in the typical and atypical clinic AN at different stages of the disease, higher efficiency of treatment was found in patients with typical AN.Summary: needs further search of objective criteria for atypical AN timely diagnosis and differential diagnosis of AN with other diseases associated with underweight and oligo-amenorrhea.